Lucy Orta. - Bolton, Andrew; Bourriaud, Nicolas; Damianovic, Maia; Orta, Jorge; Orta, Lucy; Pinto, Roberto; Virilio, Paul (London : Phaidon Press Limited London, 2003)
Lucy Orta's work examines the social bonds within communities and the relationships between individuals and their environments. In the early 1990s Orta began a series of works that combined architecture, fashion and social activism. These works took the form of prototype clothing and portable shelters for emergency situations. Orta's work has since grown to incorporate interdisciplinary workshops, contemporary dance and other actions that explore notions of identity, shared space and networking. These projects include collaborations with such marginalized groups as the unemployed, the homeless and immigrants. Italian curator Roberto Pinto traces the development of Orta's work and the social and political factors that her projects are a response to . French critic and curator Nicolas Bourriaud discusses with Orta her working practices. Maia Damianovic examines in detail the work 70 x 7 The Meal, a dinning project for an infinite number of discussions and encounters. For the Artist's Choice Orta has selected a texts by her husbands Argentinian artist Jorge Orta with whom she frequently collaborates, and by French philosopher Paul Virilio who's interests in urbanism and new technologies reflect her own. Orta's writings include preparatory drawings and diaries that record her projects, and an interview with Paul Virilio.
biog., tent., bibliog. p. 146-158
Engels
boek
Keywords: Orta, Lucy